(untitled) (Asian Journal of Social Science Studies, 2022)
It is very important to implement sex education for college students who are in the important period of adolescent development. Good sex education has an important influence on the establishment of individual self-concept and the formation of perfect personality. The mission of colleges and universities is to cultivate students’ comprehensive and healthy development, and they should take the responsibility of being the main force in implementing sex education for college students. At present, only one-third of universities in China have held lectures related to sex education, and no more than 10% of universities have offered and are offering related courses. Overall, there is a serious lack of systematic and comprehensive sex education in China’s colleges and universities, and the solution to this problem requires the collaboration of society, schools and parents.